A facile approach for achieving an effective dual sorption ability of Si/SH/S grafted sodium montmorillonite1. Issue 71 (2nd August 2015) - Chen, Hsuan-Hsuan; Thirumavalavan, Munusamy; Lin, Fang-Yu; Lee, Jiunn-Fwu
<x xml:space="preserve">Abstract</x> In this study, sodium montmorillonite was functionalized with SH, S and Si functional groups using four different soil modifiers for an effective uptake of both organic and inorganic pollutants.